2005
DOI: 10.1128/jb.187.18.6317-6323.2005
|View full text |Cite
|
Sign up to set email alerts
|

Complex Transcriptional Control Links NikABCDE-Dependent Nickel Transport with Hydrogenase Expression in Escherichia coli

Abstract: Escherichia coli requires nickel under anaerobic growth conditions for the synthesis of catalytically active NiFe hydrogenases. Transcription of the NikABCDE nickel transporter, which is required for NiFe hydrogenase synthesis, was previously shown to be upregulated by FNR (fumarate-nit rate regulator) in the absence of oxygen and repressed by the NikR repressor in the presence of high extracellular nickel levels. We present here a detailed analysis of nikABCDE transcriptional regulation and show that it close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(135 citation statements)
references
References 48 publications
3
132
0
Order By: Relevance
“…A nickeldependent regulator, NikR, has been identified in the genomes of D. vulgaris Hildenborough and Desulfovibrio desulfuricans G20, and putative binding sites for this regulator were identified upstream of genes encoding Ni transport systems (28 1 Hase synthesis between the H 2 /S medium and the other conditions suggests that hydrogen may induce a high-affinity uptake system for Ni, which is able to scavenge the low levels of Ni in the Fe-only medium in order to support a high expression level of this Hase, and that this system is not present in the other conditions. In Escherichia coli, it was recently shown that transcription of the nickel transport system NikABCDE is regulated in order to match the Hase expression level of the cell (32). Regarding the effect of Ni on the [NiFeSe] Hase, this protein is not detected, by activity-stained gel or Western blotting, in cells grown in media containing FeϩNi.…”
Section: Analysis Of Periplasmic D Vulgaris Hildenborough Hydrogenasmentioning
confidence: 94%
See 1 more Smart Citation
“…A nickeldependent regulator, NikR, has been identified in the genomes of D. vulgaris Hildenborough and Desulfovibrio desulfuricans G20, and putative binding sites for this regulator were identified upstream of genes encoding Ni transport systems (28 1 Hase synthesis between the H 2 /S medium and the other conditions suggests that hydrogen may induce a high-affinity uptake system for Ni, which is able to scavenge the low levels of Ni in the Fe-only medium in order to support a high expression level of this Hase, and that this system is not present in the other conditions. In Escherichia coli, it was recently shown that transcription of the nickel transport system NikABCDE is regulated in order to match the Hase expression level of the cell (32). Regarding the effect of Ni on the [NiFeSe] Hase, this protein is not detected, by activity-stained gel or Western blotting, in cells grown in media containing FeϩNi.…”
Section: Analysis Of Periplasmic D Vulgaris Hildenborough Hydrogenasmentioning
confidence: 94%
“…Interestingly, the genes coding for the [ Gene regulation by both Fe and Ni in prokaryotes is well documented (2,12,19). In the particular case of Hases, Ni is required for complete maturation of [NiFe] Hases (32), and transcriptional regulation by Ni has been shown, for example, in Bradyrhizobium japonicum (22) and in Methanothermobacter marburgensis. In the latter organism, growth in Ni-limited conditions leads to increased expression of the Ni-free Hase H 2 -forming methylenetetrahydromethanopterin dehydrogenase (Hmd) and strongly decreased expression of the [NiFe] Hase F 420 -reducing hydrogenase (Frh) (1).…”
mentioning
confidence: 99%
“…Although deletion of the genes for the Nik importer abrogates hydrogenase activity (43), it does not affect the response of NikR to exogenous Ni(II), suggesting that metallochaperones sequester Ni(II) for hydrogenase maturation at the transporter (42,53). Given that disruption of slyD impacts the activity of NikR as well as hydrogenase maturation, it is likely that its role is not just as a source of nickel for the hydrogenase enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Under anoxic conditions the Nik transporter is expressed to establish a supply of nickel that meets the demands of the [NiFe]-hydrogenase enzymes (1,53). Deletion of slyD caused a down-regulation of nikA transcription, with or without Ni(II) supplementation of the media.…”
Section: Discussionmentioning
confidence: 99%
“…Once in E. coli's periplasm, nickel import through the inner membrane proceeds via a unique ATP-Binding Cassette (ABC)-type transporter called Nik-ABCDE encoded by the nik operon [7]. It is suggested to be a hydrogenase-specific nickel transporter [8] and insertion mutations in the nik operon completely abolish [NiFe] hydrogenase activity [9]. Its expression is under the positive control of the oxygen sensor Fumarate Nitrate reductase Regulator (FNR) [10], which forms a DNA-binding dimer during anaerobic growth, and is negatively controlled by the transcriptional metalloregulator NikR in the presence of excess nickel [11].…”
Section: Introductionmentioning
confidence: 99%